Book Review: The Rights of Refugees Under International Law - Sims, Helen (Victoria University of Wellington Law Review, 2006)
This article is a book review of James C Hathaway The Rights of Refugees Under International Law (Cambridge University Press, New York, 2005) (1200 pages) NZ$155. In the belief that a comprehensive text on the position of refugees under international law was lacking, Hathaway has produced a book seeking to explore the nexus between human rights and refugee rights at international law, and to argue for a dynamic and purposive interpretation of the Convention Relating to the Status of Refugees. Sims praises the book's accessibility, although it is conceded by Hathaway that the book will quickly be out of date due to the area of law undergoing rapid change. Nonetheless, Sims concludes that the book is comprehensive and remains a good place to start research. By linking refugee rights to international human rights law, Hathaway provides a stronger normative basis for arguing for the continued protection of refugees under international law.